A multi-objective vehicle routing problem with simultaneous pickup and delivery and ecological considerations - Islam, Kingshuk Jubaer (2020)
Reducing CO2 emissions in transport and logistics is currently a critical goal in the field of vehicle routing as organisations are now more willing to make strategic decisions in pursuit of sustainability. However, these strategic decisions are often taken without a clear understanding of the relevant operational costs. This thesis aims to bridge the gap between strategic decisions on CO2 emissions reduction and operational decisions on the optimal routes with respect to distance travelled. Multi-objective optimisation - which provides a framework for simultaneously pursuing the best outcomes in these disparate objectives - is the most appropriate methodology to tackle this problem.